MANAJEMEN KEDISIPLINAN SISWA DI SD IT NUR HIDAYAH - Titis Sukmawati; Choirun Nisa; Mardiyah Umi; Sofia Amalia; Abel Akmalia (LPPM STAI Muhammadiyah Probolinggo, 2025)
School discipline creates a conducive and effective learning atmosphere therefore all students must adhere to the rules with great discipline so that the teaching and learning process runs smoothly. However, in fact, many students ignore the rules and regulations in the school environment. This study aims to describe: 1) planning discipline among students of SD IT Nur Hidayah, 2) organizing student discipline at SD IT Nur Hidayah, 3) implementing student discipline at SD IT Nur Hidayah, 4) supervising student discipline at SD IT Nuur Hidayah, and 5) monitoring and evaluating student discipline at SD IT Nur Hidayah. The approach used in this research is descriptive qualitative, because the data collected and analyzed are qualitative. The results of the study show that the success of enforcing student discipline at SD IT Nur Hidayath is highly dependent on the integration of five managerial aspects, namely planning, organizing, implementing, supervising, and monitoring and evaluating. With the involvement of all parties and integrated management, SD IT Nur Hidayah Surakarta has succeeded in creating a conducive educational environment in shaping students' disciplinary character, responsibility, and spirituality holistically.